2023
DOI: 10.1002/vms3.1173
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus antigen omp25 vaccines: Development and targeting based on Lactococcus lactis

Somaye Tirbakhsh Gouran,
Abbas Doosti,
Mohammad Saeid Jami

Abstract: Background Most Brucella infections take place on mucosal membranes. Therefore, creating vaccinations delivered through the mucosa may be crucial for managing brucellosis. Consequently, we assessed the efficacy of a recombinant oral antigen delivery system based on Lactococcus lactis for Brucella abortus omp25 antigen. Method Oral vaccinations with L. lactis transformed with pNZ8148 variants encoding for omp25 (pNZ8148:omp25) and free‐pNZ8148 were administered to mice. On day 30, following immunization in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the present case, a noteworthy decrease in bacterial load has been seen in the mice administered with L. lactis -pNZ8148-Usp45- Omp10 , indicating that a live vector vaccine can potentially mitigate bacterial colonization. Previous studies have elucidated the inherent characteristics of live vector vaccines in inducing a specific immune response against antigens associated with various illnesses (Diaz-Dinamarca et al 2020 ; Gouran et al 2023 ). The results of this study indicate that the use of L. lactis -pNZ8148-Usp45- Omp10 as a means of expressing vectors has the potential to provide cost-effective, easily administered, and efficacious live oral vaccines for the prevention of B. abortus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, a noteworthy decrease in bacterial load has been seen in the mice administered with L. lactis -pNZ8148-Usp45- Omp10 , indicating that a live vector vaccine can potentially mitigate bacterial colonization. Previous studies have elucidated the inherent characteristics of live vector vaccines in inducing a specific immune response against antigens associated with various illnesses (Diaz-Dinamarca et al 2020 ; Gouran et al 2023 ). The results of this study indicate that the use of L. lactis -pNZ8148-Usp45- Omp10 as a means of expressing vectors has the potential to provide cost-effective, easily administered, and efficacious live oral vaccines for the prevention of B. abortus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Viral, bacterial, and parasite antigens have been successfully produced in L. lactis , a bacterium often used in research. These recombinant strains have shown the ability to effectively transfer antigens to the intestines’ mucosal areas, eliciting a targeted immune response (Gouran et al 2023 ). Furthermore, studies have shown evidence that L. lactis can endure transit through the gastrointestinal system in both animal models and human subjects without establishing colonization (Song et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The necessity of rapid development of vaccine formulations, especially during the SARS-CoV-2 epidemic, also accelerated the process of recombinant production of antigenic proteins [21]. In our study, following the recombinant production of Omp25 (rOmp25), known to possess effective virulence characteristics [22][23][24], and the newly discovered EipB protein [25], their nanoformulations were prepared by encapsulating them into the biocompatible and biodegradable PLGA nanoparticles. Subsequently, the biocompatibility and immunogenic response of these nanoformulations was evaluated comparatively both in vitro and in vivo for the first time in the literature.…”
Section: Introductionmentioning
confidence: 99%